Evaluasi Kebijakan Pembangunan Frontage Roads Dalam Mengurangi Kemacetan Lalu Lintas Di Kota Surabaya - pramono, sapto (Fakultas Ilmu Administrasi Universitas Dr. Soetomo, 2019)
The number of motorized vehicles in major cities in Indonesia is increasing, including also the city of Surabaya with a population of more than 3 (three) million, which tends to have an impact on the increase in traffic density. Increasing the density of traffic will increase the number of vehicles, causing a decrease in vehicle speed compared to the planned speed for each function and role of the road.This study aims to determine the volume of vehicles or traffic flows that pass on the frontage road road. Furthermore, the purpose of this study is to provide an overview of the performance of the road after the opening of the frontage road on both the east and the west side.Â This evaluation examines the benefits of operating frontage road, how useful it is to reduce traffic congestion on Jalan Wonokromo and Jaan Ahmad Yani. Jalan Wonokromo and Jalan Ahmad Yani are two-way primary arterial roads (with separating directions) as a link between the cities of Surabaya and Sidoarjo and Mojokerto. The results of this evaluation are expected to be useful as a material consideration, by policy makers in the field of transportation both in terms of management and traffic engineering.